2010
DOI: 10.1002/cbdv.201000194
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Binding of Some New Lipophilic Gadolinium  DTPA Complexes to Human Serum Albumin. A Structure–Affinity Relationship

Abstract: Four Gadolinium⋅DTPA complexes bearing long lipophilic alkyl chains were synthesized: two bis[amide] and two 4-substituted derivatives. In two of them (one bis[amide] and one 4-substituted), the alkyl chain ends with a carboxylate function. Their relaxometric properties in H₂O show the self aggregation of Gd⋅DTPA-BdodecylAmide, the better stability of the 4-substituted derivatives vs. Zn transmetallation, and the very good stability of Gd⋅(4-(carboxyundecylisothiourea-Bz)DTPA). Amongst the four compounds, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Comprehensive explanation of the parameters explaining the observed stability despite a decreased number of a carboxylate available for Gd 3+ complexation is beyond the scope of this work but the following could be considered: (i) ester groups in the polymer may possibly offset the loss of these carboxylate groups or (ii) perhaps the entropy of the system limits the Gd 3+ dissociation. However, and to confirm this trend, future in vitro release study should be undertaken in more complex mediums like human serum or PBS completed with physiologically relevant concentrations of ZnCl 2 (0.03 wt %) and albumin (4 wt %) to evaluate the influence of proteins and cations on the MRI-PCLs complex stability. , One should also consider future in vivo implantation to evaluate the possible influence of enzymes, macrophages, and transient changes in pH (especially pH changes during inflammation) that may appear in vivo.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Comprehensive explanation of the parameters explaining the observed stability despite a decreased number of a carboxylate available for Gd 3+ complexation is beyond the scope of this work but the following could be considered: (i) ester groups in the polymer may possibly offset the loss of these carboxylate groups or (ii) perhaps the entropy of the system limits the Gd 3+ dissociation. However, and to confirm this trend, future in vitro release study should be undertaken in more complex mediums like human serum or PBS completed with physiologically relevant concentrations of ZnCl 2 (0.03 wt %) and albumin (4 wt %) to evaluate the influence of proteins and cations on the MRI-PCLs complex stability. , One should also consider future in vivo implantation to evaluate the possible influence of enzymes, macrophages, and transient changes in pH (especially pH changes during inflammation) that may appear in vivo.…”
Section: Results and Discussionmentioning
confidence: 99%
“…18 The lengthening of the molecular reorientational time may be pursued through the set-up of reversible binding interactions with suitable interacting species. [19][20][21] The three complexes whose structures are reported in Scheme 1 represent highly hydrophilic systems without any specific ability of binding to endogenous molecules able to affect, in a significative amount, their relaxivities. 22 With the aim of exploring possible routes to form supramolecular systems endowed with a lengthening of the reorientational motion in respect to the parent complex, we considered the possibility of exploiting the hydrophobic characteristic of the tetra-aza macrocyclic moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many efforts have been devoted in the last years to optimize the relaxometric properties and the HSA binding affinities of the CA (in order to attain improved contrast enhancement characteristics) [18][19][20][21], to date, only one blood pool Gd-based CA has entered into clinical practice. We have recently shown that, exploiting the magnetic field-dependence of the Gdcomplexes relaxivity, intermediate MW Gd-based agents show greater performance at 1T [22].…”
Section: Introductionmentioning
confidence: 99%